The determinants of capital structure among select Sub-Saharan African countries. - Gwatidzo, Tendai (My University, 2009)
This thesis examines the determinants of capital structure in Sub-Saharan Africa. It looks at three related issues. The first issue is the financing decisions of firms, that is, the choice between debt and equity. It investigates the extent to which firm characteristics affect the way African firms (in Ghana, Kenya, Nigeria, South Africa and Zimbabwe) raise capital. Secondary data from financial statements for listed firms as well as from the World Bank’s Investment Climate surveys are used. The main results from this part of the thesis are: firms in Africa are roughly leveraged to the same extent as those in emerging economies like Mexico, Thailand, Brazil, South Korea, Malaysia and Turkey; firms in Sub-Saharan Africa tend to be heavily dependent on internal finance and where they use debt, they tend to overly rely on short-term debt to finance their investment activities. We also find that, across the sample countries, firm characteristics like profitability and asset tangibility are generally negatively related to leverage. The evidence from our results suggests that heterodox variables like education, ethnicity of majority owner and location of a firm within a given country are not as important when it comes to raising capital. The second issue relates to the determinants of corporate debt choice. Using data from the World Bank’s Investment Climate surveys we investigate the decision of the African firms (in Ghana, Kenya, Nigeria and South Africa) to fill their borrowing needs. For our purposes we categorize debt sources into bank debt and non-bank debt. We find that most firms in Africa tend to use bank debt to finance additional investment. About 70% of total incremental debt used by firms in the sample countries comes from banks as loans. This confirms the hypothesis that bank debt dominates other forms of debt. The use of bank debt increases with firm size: we find that larger firms tend to use more bank debt as compared to smaller ones. This confirms the argument that smaller firms tend to face severe difficulties when it comes to accessing finance. This is because they lack the requisite reputation that banks or any other suppliers of funds require. We also find that debt preference and use tend to increase with firm size and age. We find mixed results iii when it comes to the impact of profitability and asset tangibility on debt preference. We do not find ample evidence on the impact of heterodox variables on debt choice. The third issue focuses on the supply-side of capital, relative to the first two issues explained above that dwelt on the demand side. In order to better understand the supplyside of finance we analyze a number of financial development indicators. We compare the indicators among the sample countries, across different countries, emerging economies and developed economies. We find that the stock markets and financial intermediaries in Africa, even though still underdeveloped, are fast growing. When it comes to legal systems in Africa, we find that contract enforcement in African countries is inefficient as compared to a number of emerging and developed economies. This, we suggest, may be one reason why firms in Africa tend to rely heavily on internal finance and short-term debt rather than external finance and long-term debt.